Embodied learning and new physical activity in mid- and later life. Issue 5 (20th October 2017) - Griffin, Meridith
Abstract: A disconnect exists between discursive imperatives to age 'well' by way of engagement in physical activity, and the lived experience of many adults who do not meet minimum recommendations for activity participation. This disconnect prompted an investigation of the experiences of those who had made the choice to engage in physical activity in mid-to later life. In this study, in-depth interviews were done with ten adult newcomers to different physical activity/sport settings (recreational team, individual lifestyle, group and competitive). The objective was to explore the perspectives and experiences of individuals either beginning or returning to physical activity participation in mid-to later life. Here, the focus is on the ways in which participants talked about becoming absorbed in their new chosen activity. Drawing from contemporary theory focusing on embodied learning, findings reveal the ways in which new styles of moving were experienced by participants – as they confront emotions and processes including vulnerability, vigilance and enculturation that emerged when challenged by new kinaesthetics. These findings are linked back to potential avenues and/or strategies through which more older adults may be encouraged to view new physical activities as desirable, accessible and achievable – even when a true beginner.